If f(x) = 3x^2 -4 and g(x) = 2x -1, what is (f of g)(x)?

2 Answers

crmhaske's profile pic

crmhaske | College Teacher | (Level 3) Associate Educator

Posted on

(f of g)(x)=f(g(x))

`f(g(x))=3(2x-1)^2-4`

`=3(4x^2-4x+1)-4`

`=12x^2-12x+3-1`

`=12x^2-12x+2`

Sources:

1 reply Hide Replies

pramodpandey's profile pic

pramodpandey | College Teacher | (Level 3) Valedictorian

Posted on

We have given

`f(x)=3x^2-4 `   and `g(x)=2x-1` ,We wish to find  `fog(x)`

`fog(x)=f(g(x))`

`=f(2x-1)=3(2x-1)^2-4`

`=3(4x^2-4x+1)-4`

`=12x^2-12x+3-4`

`=12x^2-12x-1`